2003
DOI: 10.1167/iovs.02-0952
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation in Retinal Progenitors by Glia-Derived Neurotrophic Factor and Docosahexaenoic Acid

Abstract: GDNF and DHA acted as molecular cues, counterbalancing the decision of photoreceptors to remain in or exit the cell cycle. The results strongly suggest that both factors participate in determining the number of photoreceptors in vitro, regulating the cell cycle and survival at early and late stages of development, respectively. Hence, GDNF and DHA may coordinately control the histogenesis of photoreceptors in the retina by modulating both neurogenesis and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…Finally, different species were tested, which could be relevant, because the spontaneously hypertensive rats used by Dempsey and coworkers have a higher basal progenitor cell proliferation compared with normotensive rats. 18 GDNF also stimulates proliferation of other stem/progenitor cells, notably retinal progenitor cells in vitro, 19 and neural precursors from the embryonic gut. 20 Our data indicate that this effect is mediated by receptors on the stem/progenitor cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, different species were tested, which could be relevant, because the spontaneously hypertensive rats used by Dempsey and coworkers have a higher basal progenitor cell proliferation compared with normotensive rats. 18 GDNF also stimulates proliferation of other stem/progenitor cells, notably retinal progenitor cells in vitro, 19 and neural precursors from the embryonic gut. 20 Our data indicate that this effect is mediated by receptors on the stem/progenitor cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The dentate gyrus and associated hilus of the hippocampal formation showed a consistent increased thickness in proliferative zones, with a decreased size of target regions, which could reflect an inhibition or delay of neurogenesis, or disruption in postmitotic migration (27). Other recent studies have shown that DHA promotes cellcycle exit in retinal neuroprogenitor cells in culture (43) and promotes differentiation of neural stem cells into neurons by promoting cell-cycle exit and suppressing cell death (28). Restriction of (n-3) fatty acids leads to reduced DHA, increased (n-6) fatty acids, and increased dopamine in fetal brain cortex (44) and over-expression of dopamine receptor genes (45).…”
Section: Introductionmentioning
confidence: 87%
“…Cultures from PN0 retinas treated at day 2 with or without RA showed similar percentages of BrdUpositive cells (Table 4). Since by day 2 few photoreceptor progenitors remain in the cell cycle, we added RA at day 0, when many progenitors still are proliferating 46 ; this addition decreased slightly, though not significantly, the percentage of BrdU-labeled cells compared to controls (Table 4).…”
Section: Ra Effect On Cell Cycle Exitmentioning
confidence: 99%